Studi Pengaruh Temperature dan Pembuatan Beton Massa dengan Ketebalan 4 Meter (Studi Kasus : Proyek Gunawangsa Tidar Apartement Surabaya) - Wardhani, Fitri Swastika; Koespiadi, Koespiadi (Ge-STRAM: Jurnal Perencanaan dan Rekayasa Sipil, 2019)
Building a building with a large and large number of foundations requires a mass casting method. In mass casting work requires observation and analysis of temperature in order to find out the peak temperature and no thermal cracks occur. In this Final Project aims to determine the effect of mass concrete temperature on the raft foundation of the Surabaya Gunawangsa Tidar Aparment Project. The project has 25 types of raft foundations, but the ones with large dimensions and mass casting are pile cap 114 and pile cap 119. Mass casting is carried out in a full day so after casting it is necessary to observe the effect of concrete temperature. The effect of temperature observed was peak temperature, temperature difference, and statistical hypothesis testing. In general, the peak temperature at ijinkam is 78.20˚ C with a difference in temperature of 20˚C. Observations on pile cap 114 and pile cap 119 are safe and have no thermal cracks.